Analisis Pengaruh Faktor Lingkungan Sosial dan Lingkungan pada Keputusan Investasi Perusahaan: Pendekatan ESG dalam Manajemen Keuangan - Andi Primafira Bumandava Eka; Henky Hendrawan; Nurwita Nurwita; Pandu Adi Cakranegara; Rita Zulbetti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In contemporary corporate finance, the integration of Environmental, Social, and Governance (ESG) factors has emerged as a pivotal consideration in investment decision-making. This article delves into the analysis of how social and environmental factors influence corporate investment decisions, employing an ESG approach within financial management. Drawing upon an extensive literature review, this paper synthesizes key insights from existing research on the intersection of ESG factors and financial decision-making processes of corporations. The literature underscores the growing recognition of the significant impact that social and environmental considerations wield on investment decisions, transcending mere financial metrics. By examining the interplay between social and environmental factors and investment decisions, this article aims to provide a comprehensive understanding of the mechanisms through which corporations incorporate ESG considerations into their financial strategies. It explores the various frameworks and methodologies used to assess and integrate ESG factors into investment decision-making processes, shedding light on the evolving landscape of sustainable finance. This research contributes to the burgeoning discourse on sustainable finance by offering insights into how corporations navigate the complex interplay between financial objectives and broader social and environmental imperatives. Through empirical analysis and theoretical frameworks, this article seeks to inform policymakers, investors, and corporate stakeholders about the implications of incorporating ESG considerations into investment decision-making processes. Keywords: Environmental, Social, Governance, ESG, Investment Decisions, Financial Management.